THE PROCESS OF DEVELOPING LIFELONG LEARNING SKILLS IN THE 21ST CENTURY ACCORDING TO BUDDHIST PRINCIPLES FOR MONKS IN THE SANGHA ADMINISTRATION REGION 12 - Titakuno (Dissungworn), PhrakrupaladRut; Ngamprakhon , Sin; Chumnisart, Booncherd (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to 1) study the status of lifelong learning skills in the 21st century of monks in the Sangha Region 12, 2) develop a process for developing lifelong learning skills in the 21st century based on Buddhist principles, and 3) evaluate the process for developing lifelong learning skills in the 21st century based on Buddhist principles. This research was a mixed-method research. The quantitative research used a sample of 132 monks. The qualitative research interviewed key informants and organized focus group discussions with experts. The research instruments were questionnaires, interview forms, and focus group discussion manuals. The research data were analyzed by using frequency, percentage, mean, standard deviation, and content analysis. The results of the research found that 1) the status of lifelong learning skills in the 21st century of monks in the Sangha Region 12 was at a high level overall. 2) The process of developing lifelong learning skills in the 21st century based on Buddhist principles was at a high level. It was a process of developing lifelong learning skills integrated with the 4 Iddhip da: (1) setting learning goals, (2) selecting appropriate learning methods, (3) practicing activities, (4) evaluating learning outcomes, (5) learning indicators, and 3) the results of the evaluation of the process of developing lifelong learning skills in the 21st century according to Buddhist principles were at a high level overall. It could be used to develop lifelong learning skills in the 21st century with the 4 Iddhip da for monks in the 12th Sangha Administrative Region effectively.